The Polymorphism rs2725220 Is Associated with Hyperuricemia in the Korean Population - Jae Woong Sull; Seung-Ju Yang; Soriul Kim; Sun Ha Jee (Genomics & Informatics)
Elevated serum uric acid levels are associated with a variety of adverse health outcomes, including gout, hypertension, diabetes mellitus, metabolic syndrome, and cardiovascular diseases. Several genome-wide association studies on uric acid levels have implicated the ATP-binding cassette, subfamily G, member 2 (ABCG2) gene as being possibly causal. We investigated an association between the single-nucleotide polymorphism (SNP) rs2725220 in the ABCG2 gene and uric acid levels in the Korean population. A total of 991 subjects in Seoul City were used for a replication study with ABCG2 SNP rs2725220. The rs2725220 SNP in the ABCG2 gene was associated with mean uric acid levels (effect per allele 0.25 mg/dL, p < 0.0001). Subjects with the GC/CC genotype had a 1.78-fold (range, 1.22- to 2.62-fold) higher risk of having abnormal uric acid levels (≥7.0 mg/dL) than subjects with the GG genotype. When analyzed by gender, the association with ABCG2 was stronger in men than in women. The association with ABCG2 was much stronger in male subjects with body mass index (BMI) ≥ 26.4 (odds ratio, 5.09; 95% confidence interval, 2.41 to 10.8) than in male subjects with BMI < 26.4. This study clearly demonstrates that genetic variations in ABCG2 influence uric acid levels in Korean adults.